Cultural learning in virtual heritage: An overview - Ibrahim N.; Mohamad Ali N.; Mohd Yatim N.F. (2023)
The aim of this paper is to present the overview of cultural learning in virtual heritage. In the past, works done on virtual heritage were mostly focused on replicating and visualizing heritage objects for presentation using virtual reality. However, accurate and realistic representation of heritage objects is not enough when it comes to cultural learning in virtual environment. This paper attempts to identify issues that impede cultural learning in virtual environment. In order to develop a virtual environment that is able to facilitate cultural learning, we argue that there is a need to understand what the end users really want to know when it comes to learning culture. We propose a thorough user study to be carried out at the beginning of virtual heritage project development and discuss the outline of our intended approach. 2011 Springer-Verlag.